Cześć!
Szczegółowe wyjaśnienie:
a)
[tex]2x + 9 = 1 \\ 2x = 1 - 9 \\ 2x = - 8 \\ x = - 4[/tex]
b)
[tex]6 x- 25 = - 25 \\ 6x = 0 \\ x = 0[/tex]
c)
[tex]8 - (4x - 12) = 8x - (3x - 2) \\ 8 - 4x + 12 = 8x - 3x + 2 \\ 20 - 4x = 5x + 2 \\ - 4x - 5x = 2 - 20 \\ - 9x = - 18 \\ x = 2[/tex]
d)
[tex] - (x + 1) + 8x = 5x - 9 \\ - x - 1 + 8x = 5x - 9 = \\ 7x - 1 = 5x - 9 \\ 7x - 5x = - 9 + 1 \\ 2x = - 8 | \div 2 \\ x = - 4[/tex]
e)
[tex]2x - 2 + x = 3x - 1 \\ 3x - 2 = 3x - 1 \\ - 2 = - 1[/tex]
f)
[tex]4x - 1 = 3(x + 1) + (x - 4) = \\ 4x - 1 = 3x + 3 + x - 4 \\ 4x - 1 = 4x - 1 \\ x \in \mathbb{R}[/tex]